Vpr-induced cell cycle arrest is conserved among primate lentiviruses. - Planelles, V (1996)
We previously reported that expression of human immunodeficiency virus type 1 strain NL4-3 (HIV-1(NL4-3))vpr causes cells to arrest in the G2 phase of the cell cycle. We examined the induction of cell cycle arrest by other HIV-1 isolates and by primary lentiviruses other than HIV-1. We demonstrate that the vpr genes from tissue culture-adapted or primary isolates of HIV-1 are capable of inducing G2 arrest. In addition, we demonstrate that induction of cell cycle arrest is a conserved function of members of two other groups of primate lentiviruses, HIV-2/simian immunodeficiency virus strain sm (SIVsm)/SIVmac and SIVagm. vpr from HIV-1, HIV-2, and SIVmac induced cell cycle arrest when transfected in human (HeLa) and monkey (CV-1) cells. vpx from HIV-2 and SIVmac did not induce detectable cell cycle arrest in either cell type, and SIVagm vpx was capable of inducing arrest in CV-1 but not HeLa cells. These results indicate that induction of cell cycle perturbation is a general property of lentiviruses that infect primates. The conservation of this viral function throughout evolution suggests that it plays a key role in virus-host relationships, and elucidation of its mechanism may reveal important clues about pathology induced by primary lentiviruses.